Estimating completeness of cancer registration: an empirical evaluation of the two source capture-recapture approach in Germany. Issue 4 (August 1995) - Brenner, H; Stegmaier, C; Ziegler, H
Abstract : STUDY OBJECTIVE–In recent years, capture-recapture methods have become increasingly popular in estimating completeness of disease registries. This study aimed to assess the performance of the two source capture-recapture method in estimating the completeness of cancer registration. DESIGN–The study was conducted in the population based cancer registry of Saarland, Germany, for which there are three main sources of notifications: reports by clinicians and pathologists, and death certificates. For groups of cases notified by one of the three sources, known completeness of registration by the other two sources was compared with the corresponding two source capture-recapture estimates. PATIENTS–A total of 16, 020 patients notified to the cancer registry in 1970, 1975, 1980, and 1985 were included in the analysis. MAIN RESULTS–There was a tendency towards underestimation of completeness of notifications from pathologists and death certificates for patients notified by clinicians which was essentially confined to the older age groups. In contrast, capture-recapture methods tended to overestimate completeness of notifications from clinicians and death certificates for patients notified by pathologists. This overestimation was observed consistently in all age groups and for all of the most common cancer sites. Nevertheless, deviations of estimated completeness from known completeness were generally small or moderate. Agreement between estimated and known completeness was closest for patients notified by death certificates, although completeness was somewhat underestimated in patients above age 75. The observed patterns are in agreement with knowledge on clinical aspects and clinical management of cancer patients and with the circumstances of cancer registration in Saarland. CONCLUSIONS–Careful application of capture-recapture methods may provide an alternative to traditional approaches for estimating completeness of cancer registration.